Does Healthy-Chilli Cultivation Increase Productivity and Trade Value for Farmers? - Beauty Martha Lingga; Irham Irham; Hani Perwitasari (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2026)
Healthy chilli farming has the potential to increase both the output and income of farmers in improving farmer’s welfare through GAP implementation. The welfare of farmers encompasses more than just income and production, hence, the Farmer’s Terms of Trade (FTT) serve as a reference point for household prosperity in Indonesia. This research aims to: (1) compare the productivity of chilli farmers, (2) examine the farmer’s terms of trade, and (3) analyze the impact of productivity and other factors on the farmer’s terms of trade associated with three farming methods: healthy, semi-healthy, and conventional farming systems. The study was conducted in Sleman Regency, Indonesia, a region that has been implementing healthy-chilli farming system since 2021. A total of 106 farmers were interviewed, distributed across 6 areas known for their significant chilli production. The respondents were selected through a simple random sampling approach. The FTT is assessed through household income and subsistence terms of trade. The comparison of farmer productivity was analyzed using a Kruskal-Wallis H test. The findings indicate that the productivity of healthy-farming is higher than other two chilli farming systems. The FTT for healthy- farming is higher and classified as prosperous, while others do not yet reach prosperous level. Moreover, subsistence terms of trade of healthy and conventional farming statistically different. The increase of FTT was significantly affected by productivity, planting area, and price of chilli, while the number of family member, non-family labor cost, and household expenditures can decrease the FTT.